VISPA: Direct Access and Execution of Data Analyses for Collaborations. (April 2015) - von Asseldonk, Daniel; Erdmann, Martin; Fischer, Robert; Glaser, Christian; Müller, Gero; Quast, Thorben; Rieger, Marcel; Urban, Martin
Abstract: The VISPA project provides a graphical frontend to computing infrastructures. Currently, the focus of the project is to give an online environment for the development of data analyses. Access is provided through a web GUI, which has all functionality needed for working conditions comparable to a personal computer. This includes a new preference system as well as user configurable shortkeys. As all relevant software, data and computing resources are supplied on a common remote infrastructure the VISPA web framework offers a new way of collaborative work where analyses of colleagues can be reviewed and executed with just one click. Furthermore, VISPA can be extended to the specific needs of an experiment or other scientific use cases. This is presented in the form of a new GUI to the analysis framework Offline of the Pierre Auger collaboration.